Analisis Kualitas Sumber Daya Manusia, Profesionalisme Kerja, Dan Komitmen Terhadap Kinerja Karyawan Pada Badan Layanan Umum Daerah Sistem Penyediaan Air Minum (BLUD-SPAM) Kabupaten Nagekeo - Pogo, Maria Goreti Je; Langga, Lambertus; Tanusi, Gabriel (Program Studi Manajemen Universitas Flores, 2021)
The purpose of this study is to determine the influence of the quality of the human resources, work professionalism and commitment to employee performance BLUD SPAM Nagekeo District, and to find out the most dominant effect on the performance of employees of the Regional Public Service Agency Nagekeo District Drinking Water Supply System. The type of research used in this study is researchQuantitative. The data source is primary and secondary data, with data collection through the dissemination of questionnaires. respondents in this studyemployees of the regional public service agency district drinking water supply system Nagekeo numbered 52 respondents. Data analysis techniques used i is a test of data quality and multiple linear regression techniques. Determination co-fisian test (R2) indicates that the influence of variables independent of dependent variables is 46.6% meaning that the presentation of factors of human resource quality, work professionalism and commitment jointly affect the performance of employees in blud offices SPAM Nagekeo Regency While the remaining 53.6 % described other factors or that do not appear in this research hypothesis Basedon the results of simultaneous test F shows that Fcalculate > Ftabel as large as 15,705>2.80 and the accepted hypothesis is the Hr Quality Factor (X1), Professionalism of work (X2), commitment (X3) have a simultaneous effect on the employee performance (Y), the t test showed that the most dominant variable affect employee performance is a variable of professionalism of work4,474 and a commitment of 4,089 with a sig value. 0.000 and 0.000 smaller than other variables.